The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3390/v7122948
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Human Rhinoviruses and Enteroviruses Highlights Their Diversity in Sub-Saharan Africa

Abstract: Human rhinoviruses (HRVs) and enteroviruses (HEVs) belong to the Enterovirus genus and are the most frequent cause of infection worldwide, but data on their molecular epidemiology in Africa are scarce. To understand HRV and HEV molecular epidemiology in this setting, we enrolled febrile pediatric patients participating in a large prospective cohort assessing the causes of fever in Tanzanian children. Naso/oropharyngeal swabs were systematically collected and tested by real-time RT-PCR for HRV and HEV. Viruses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
(67 reference statements)
3
20
0
Order By: Relevance
“…In our study, 34% of the typed EV strains belonged to species EV-C. Although EV-C is a rather rare species in most of the world [ 3 , 7 , 8 , 49 51 ], it accounts for up to 76% of typed EV strains found in African populations [ 18 , 20 , 22 , 25 28 ]. The high proportion of EV-C subgroup C as found in our study is in accordance with findings in Cameroon and Madagascar.…”
Section: Discussionmentioning
confidence: 51%
“…In our study, 34% of the typed EV strains belonged to species EV-C. Although EV-C is a rather rare species in most of the world [ 3 , 7 , 8 , 49 51 ], it accounts for up to 76% of typed EV strains found in African populations [ 18 , 20 , 22 , 25 28 ]. The high proportion of EV-C subgroup C as found in our study is in accordance with findings in Cameroon and Madagascar.…”
Section: Discussionmentioning
confidence: 51%
“…A previous study conducted in Kilifi using the same molecular diagnostic assay reported a similar detection of non-HRV enteroviruses 38 . Further, a recent study in Tanzania observed a relatively high prevalence of non-HRV enteroviruses in NPS sample including poliovirus type 1, enterovirus-D68, A71, echovirus-6, 7, 9 , 11 and a variety of coxsackievirus serotypes 40 .…”
Section: Discussionmentioning
confidence: 95%
“…RV-B48 (RV from species B), RV-C15 (RV from species C), RV-C8 (RV from species C, isolated from a patient's serum with disseminated infection), 26 EV-D68 (respiratory EV from species D), influenza A H3N2 Victoria like, RSV subgroup B, and HCoV-OC43 (Table I) 16,[26][27][28][29] directly in reconstituted airway epithelia to prevent acquisition of cell adaptation mutations. Viral RNA copies (10 6 ) corresponding to the average load found in clinical samples [30][31][32] were used in each round of infection.…”
Section: High-throughput Sequencingmentioning
confidence: 99%